Yields and gaseous composition from slow pyrolysis of refuse-derived fuels - N. Tippayawong (2018)
Pyrolysis of refuse-derived fuels (RDF) has been experimentally conducted in a laboratory-scale, externally heated tubular reactor at temperatures in the range of 400C-700C. Combinations of solid wastes were tested in a batch operation where temperature evolution was recorded. The yields of final pyrolysis products were collected for solid char, liquid, and gas. The collected gaseous component was analyzed using gas chromatography. It was found that both the composition and temperature had a significant effect on yields of pyrolysis products. The yield of solid product was found to decrease from 55 to 49% for the RDF as the pyrolysis temperature was changed from 400C to 700C. Liquid product yield was small but found to increase with temperature. A maximum gaseous product yield of 43% was obtained at a pyrolysis temperature of 400C, which slightly declined with rising temperature. Gaseous composition also proved to vary with sample material and temperature. Percentage of HC showed a peak at 500C, whereas CO was observed to increase monotonically with increasing temperature.